Fly-fishing the north country - Perich, Shawn (Pfeifer-Hamilton, 1995)
If you enjoy the challenge of deceiving wary trout with wisps of fur and feather tied to a tiny hook, fly-fishing is for you. Fly-Fishing the North Country offers experienced anglers and novices the information they need to catch north country fish including feisty Bluegills, beautiful Brook Trout, and even monstrous Muskies. Shawn Perich has gathered the secrets of fly-fishing including tips for purchasing tackle, learning to cast, selecting the right flies, and finding fish. The book concludes with patterns for tying more than sixty flies specially designed for fishing success in northern lak.